Financial Technology, Transaction Efficiency and Financial Satisfaction: The Mediating Role of Financial Achievement - Ariel Lisna Al Syahrani; Agus Eko Sujianto; Nur Aini Latifah; Sulaiman Hasan Sulaiman (Indonesian Economic Review, 2022)
Financial technology has emerged as a powerful platform for financial activities and transactions. This study aims to investigate the role of financial technology in explaining financial satisfaction and transaction efficiency. This research also highlights the mediating role of financial achievement in its relation to financial technology, transaction efficiency, and financial satisfaction. This study adopted a quantitative study undergoing a path analysis. The research sample was approximately 250 students, which was determined purposively at the Islamic Economics Department of IAIN Tulungagung. The underlying rationale is that the course provided in the department focused on the micro and macroeconomics and the financial industry today. The findings of this study indicate that financial technology plays a crucial role in affecting transaction efficiency, financial achievement, and financial satisfaction. The study also confirms the act of financial achievement in mediating the relationship between financial technology and financial satisfaction as well as financial technology and transaction efficiency.